1996
DOI: 10.1161/01.str.27.4.650
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intracranial and Extracranial Carotid Steno-Occlusive Diseases in Taiwan Chinese Patients With MR Angiography

Abstract: A racial difference between Chinese and white patients in location of lesion in cerebrovascular steno-occlusive diseases was confirmed. About one third of symptomatic Chinese patients living in Taiwan showed small-vessel disease. Approximately 24% of patients had only extracranial carotid disease, and about 26% had only intracranial carotid tributary disease. We need a larger series of patients to confirm these findings. However, MRA might be a good screening tool for steno-occlusive cerebrovascular disease, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 25 publications
5
85
1
Order By: Relevance
“…The prevalence of carotid plaques in our data (65.4%) was higher than the findings by angiography. Previous stenosis‐based studies reported that, in Chinese stroke patients, the incidence of carotid atherosclerosis was ranging from 41.7% to 52% 16, 17, 18. In contrast, MR vessel wall imaging techniques may yield more lesion detection which may be underestimated by measuring luminal stenosis due to positive remodeling effect 19.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of carotid plaques in our data (65.4%) was higher than the findings by angiography. Previous stenosis‐based studies reported that, in Chinese stroke patients, the incidence of carotid atherosclerosis was ranging from 41.7% to 52% 16, 17, 18. In contrast, MR vessel wall imaging techniques may yield more lesion detection which may be underestimated by measuring luminal stenosis due to positive remodeling effect 19.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated prevalence of middle cerebral artery stenosis among asymptomatic Asian patients ranges from 7.2% to 29.6%, while Asian patients with ischemic stroke have a higher ICS incidence of 33% to 84% 4, 19. Further, concurrent atherosclerosis of intracranial and extracranial vessels is not uncommon in Asian populations13, 20, 21, 22; in fact, ≈20% to 50% of patients with ECS are reported to also have ICS 22, 23, 24. In this study, we found that 51.4% of patients with ECS had concurrent ICS.…”
Section: Discussionmentioning
confidence: 99%
“…13 Estimates of the responsibility of intracranial stenosis in causing stroke are 33%-50% in China. 9,21,22 Asymptomatic patients with vascular risk factors also frequently have significant degrees of intracranial stenosis. TCD sonography identified MCA stenosis in 12.6% of at-risk individuals in a study conducted in Hong Kong.…”
Section: Epidemiologymentioning
confidence: 99%